(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2012)
Polyaniline-silica (PAni-silica) composite material with 40% silica was prepared by polymerization of aniline in a medium consisting of colloidal silica, freshly prepared by hydrolysis of sodium silicate at room temperature at pH 6.5. The physico-chemical properties of both PAni and the composite material, PAni-silica were studied by FT-IR and transmission electron microscopy and measurements of Brunauer- Emmett-Teller (BET) isotherms. PAni-silica composites showed inhomogeneous pore distribution, although PAni has no significant pores. Average pore size of PAni-silica was 280 and 175 Å during adsorption and desorption of nitrogen, respectively. The interactions of PAnisilica composite and PAni with saturated hydrocarbons were investigated by inverse gas chromatography. The composite material was found to be efficient for separation of a mixture of hydrocarbons, in the range of C5-C9, owing to large BET surface area. Enthalpy of adsorption of the individual hydrocarbons was evaluated from an analysis of the retention time and the flow rate of the carrier gas. For PAni, the enthalpy of adsorption was very low; however, the value for the composite material was found to be comparable to the enthalpy of evaporation of the individual hydrocarbons. DOI: http://dx.doi.org/10.3329/bjsir.v47i3.13055 Bangladesh J. Sci. Ind. Res. 47(3), 249-256, 2012